2009
DOI: 10.1002/nbm.1395
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR metabolomics study of age profiling in children

Abstract: Metabolic profiling of urine provides a fingerprint of personalized endogenous metabolite markers that correlate to a number of factors such as gender, disease, diet, toxicity, medication, and age. It is important to study these factors individually, if possible to unravel their unique contributions. In this study, age-related metabolic changes in children of age 12 years and below were analyzed by 1H NMR spectroscopy of urine. The effect of age on the urinary metabolite profile was observed as a distinct age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 64 publications
8
70
0
2
Order By: Relevance
“…Creatinine was used to normalize for urine concentrations in our study, and urinary creatinine concentrations were not significantly correlated with log M1 in any dataset except for the spot urine samples of the training set (p = 0.01). Urinary creatinine concentrations have been reported to change with age, [49] and a significant association between creatinine concentrations and age was observed in the training set (p = 0.036 and < 0.0001 in the spot and timed urine collections, respectively) but not in the validation set. Admittedly, creatinine concentrations may influence the interpretation of the data in the training set, but it does not appear to be an important confounder in the validation set.…”
Section: Discussionmentioning
confidence: 99%
“…Creatinine was used to normalize for urine concentrations in our study, and urinary creatinine concentrations were not significantly correlated with log M1 in any dataset except for the spot urine samples of the training set (p = 0.01). Urinary creatinine concentrations have been reported to change with age, [49] and a significant association between creatinine concentrations and age was observed in the training set (p = 0.036 and < 0.0001 in the spot and timed urine collections, respectively) but not in the validation set. Admittedly, creatinine concentrations may influence the interpretation of the data in the training set, but it does not appear to be an important confounder in the validation set.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the concentrations of amino acids, citric acid cycle intermediates, and urea cycle intermediates and purine metabolites increased with age, whereas the plasma levels of fatty acids, ketone bodies and cholesterol were reduced in younger individuals. Gu et al (2009) examined age-related metabolic changes in children. Urinary samples from children ranging from newborns to 12-year-olds were analysed by NMR spectroscopy and the data sets were subjected to multivariate statistical analysis.…”
Section: Age Gender and Menstrual Cyclementioning
confidence: 99%
“…This is due to the underlying assumption of constant excretion of creatinine into urine, which generally holds except for some diseases that affect kidney function. Creatinine levels in urine also show a slight age dependence [3]. …”
Section: Data Processing and Metabolite Identificationmentioning
confidence: 99%